Alaskan native secondary school dropouts, a research report - Ray, Charles K; Ray, Charles K. ([College] University of Alaska, 1962)
"Members of the committee were selected to represent the Bureau of Indian Affairs, the Alaska State Department of Education, and the University of Alaska." Mode of access: Internet.